Interpatient variability in the pharmacokinetics of remdesivir and its main metabolite GS-441524 in treated COVID-19 subjects. (15th July 2022) - Tempestilli, Massimo; Ascoli Bartoli, Tommaso; Benvenuto, Domenico; Stazi, Giulia Valeria; Marchioni, Luisa; Nicastri, Emanuele; Agrati, Chiara
Abstract: Background: Remdesivir is the first antiviral drug against SARS-CoV-2 approved for use in COVID-19 patients. Objectives: To study the pharmacokinetic inter-individual variability of remdesivir and its main metabolite GS-441524 in a real-world setting of COVID-19 inpatients and to identify possible associations with different demographic/biochemical variables. Methods: Inpatients affected by SARS-CoV-2 infections, undergoing standard-dose remdesivir treatment, were prospectively enrolled. Blood samples were collected on day 4, immediately after ( C 0 ) and at 1 h ( C 1 ) and 24 h ( C 24 ) after infusion. Remdesivir and GS-441524 concentrations were measured using a validated UHPLC-MS/MS method and the AUC0–24 was calculated. At baseline, COVID-19 severity (ICU or no ICU), sex, age, BMI and renal and liver functions were assessed. Transaminases and estimated glomerular filtration rate (e-GFR) were also evaluated during treatment. Linear regression, logistic regression and multiple linear regression tests were used for statistical comparisons of pharmacokinetic parameters and variables. Results: Eighty-five patients were included. The mean (CV%) values of remdesivir were: C 0 2091 (99.1%) ng/mL, C 1 139.7 (272.4%) ng/mL and AUC0–24 2791 (175.7%) ng·h/mL. The mean (CV%) values of GS-441524 were: C 0 90.2 (49.5%) ng/mL, C 1 104.9 (46.6%) ng/mL, C 24 58.4 (66.9) ng/mL and AUC0–24 1976 (52.6%) ng·h/mL. The multiple regression analysis showed that age ( P <  0.05) and e-GFR ( P <  0.01) were independent predictors of GS-441524 plasma exposure. Conclusions: Our results showed a high interpatient variability of remdesivir and GS-441524 likely due to both age and renal function in COVID-19 inpatients. Further research is required to understand whether the pharmacokinetics of remdesivir and its metabolites may influence drug-related efficacy or toxic effect.